1999
DOI: 10.1099/00221287-145-11-3273
|View full text |Cite
|
Sign up to set email alerts
|

Organization of threonine biosynthesis genes from the obligate methylotroph Methylobacillus flagellatus The GenBank accession numbers for the aspC-hom-thrC-thyA gene cluster and thrB gene sequences from M. flagellatus reported in this paper are L78665 and L78666, respectively.

Abstract: The genes encoding aspartate kinase (ask), homoserine dehydrogenase (hom), homoserine kinase (thrB) and threonine synthase (thrC) from the obligate methylotroph Methylobacillus flagellatus were cloned. In maxicells hom and thrC directed synthesis of 51 and 48 kDa polypeptides, respectively. The hom, thrB and thrC genes and adjacent DNA areas were sequenced. Of the threonine biosynthesis genes, only hom and thrC were tightly linked in the order hom-thrC. The gene for thymidylate synthase (thyA) followed thrC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Wild-type B. methanolicus MGA3 (ATCC 53907) and homoserine dehydrogenase mutants have been shown to secrete substantial quantities of -glutamic acid and -lysine when grown at 50 mC in fed-batch cultures on methanol as the sole source of carbon and energy (Hanson et al, 1996 ;Lee et al, 1996). In contrast to Gram-negative methylotrophs such as Methylobacillus flagellatus (Marchenko et al, 1999) that also have been reported to secrete amino acids and vitamins, the single cell membrane of B. methano-S. B. Pluschkell and M. C. Flickinger licus should be an advantage for rapid secretion of high levels of amino acids. To maximize the yield of amino acids, the fraction of methanol carbon dissimilated as CO # must be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type B. methanolicus MGA3 (ATCC 53907) and homoserine dehydrogenase mutants have been shown to secrete substantial quantities of -glutamic acid and -lysine when grown at 50 mC in fed-batch cultures on methanol as the sole source of carbon and energy (Hanson et al, 1996 ;Lee et al, 1996). In contrast to Gram-negative methylotrophs such as Methylobacillus flagellatus (Marchenko et al, 1999) that also have been reported to secrete amino acids and vitamins, the single cell membrane of B. methano-S. B. Pluschkell and M. C. Flickinger licus should be an advantage for rapid secretion of high levels of amino acids. To maximize the yield of amino acids, the fraction of methanol carbon dissimilated as CO # must be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…B. methanolicus HSD Ϫ strain 13A52-8A66 can secrete over 60 g of L-lysine plus glutamate (glutamate) per liter, with a mass yield of 0.50 to 0.63 g/g. However, no mutants that secrete only L-lysine have been found with this approach; all simultaneously secrete significant quantities of glutamate and smaller amounts of alanine.Limited knowledge exists for most aerobic methylotrophs of the genetic basis of the regulation of pyruvate metabolism, the activity of tricarboxylic acid (TCA) cycle enzymes during rapid growth on methanol (7,13,54), and particularly regulation of the flow of carbon to amino acid biosynthesis (20,(31)(32)(33)46). To accomplish high-level L-lysine production, the percentage of carbon dissimilated to CO 2 must be minimized to generate an abundant supply of aspartate (37).…”
mentioning
confidence: 99%
“…The gene encoding homoserine dehydrogenase (hom) has been cloned and sequenced from diverse bacteria including Corynebacterium glutamicum [23], Lactobacillus lactis [14], Bacillus subtilis [22], Bacillus sp. ULM1 [16], Pseudomonas aeruginosa [5], Methylobacillus glycogens [21], Methylobacillus Xagellatus [18], Esherichia coli and Salmonella typhimurium [6] and Streptomyces sp. NRRL 5331 [7].…”
Section: Introductionmentioning
confidence: 99%